The link business: A form of organizational expression in the universities: Vinculación Empresarial y Formación Profesional - Hernández Tamayo, José Cristóbal (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The purpose of this research is to describe the impact of the linking actions of companies in higher educational institutions. The methodology was based on documentary studies and surveys applied to students and graduates of a University. The results highlight that students who participate in internship programs in organizations during their stay at universities have greater possibilities of exercising their professional practice. It is scientifically concluded that the higher educational institutions that provide internships to students in the industry increase their enrollment thanks to the incorporation to the professional practice.